2008
DOI: 10.1088/0022-3727/41/9/095404
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of the intermetallic compound Fe2TiSn

Abstract: Full-potential linearized augmented plane wave and local orbital method calculations were performed for Fe2TiSn in order to investigate the optical properties and to show the origin of the different optical transitions. It is found that the band gap is indirect for Fe2TiSn. Then our calculated reflectivity spectra are in good agreement with the experimental results. On the other hand, the contributions of various transition peaks are analysed from the imaginary part of the dielectric function. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Yabuuchi et al [12] reports a band gap of 0.07 eV and estimates that a high Seebeck coefficient (S < −200 μV K −1 ) would manifest upon n-type doping, on the order of 10 21 cm −3 . This band structure is consistent with published band structure calculations [35][36][37] that also evaluate the density of state (DOS), indicating that the conduction band is primarily comprised of Fe states.…”
Section: Band Structure Computationssupporting
confidence: 88%
“…Yabuuchi et al [12] reports a band gap of 0.07 eV and estimates that a high Seebeck coefficient (S < −200 μV K −1 ) would manifest upon n-type doping, on the order of 10 21 cm −3 . This band structure is consistent with published band structure calculations [35][36][37] that also evaluate the density of state (DOS), indicating that the conduction band is primarily comprised of Fe states.…”
Section: Band Structure Computationssupporting
confidence: 88%
“…These two alloys also show semimetallic or semiconducting properties. [4][5][6] This electron rule is similar to the 14-electron rule of chimneyladder compounds, such as MnSi 1:7 . 7,8) The 14-electron rule predicts that compounds with a VEC of 14 are semiconductors and that the valence-band occupation of those compounds is determined by just the VEC.…”
mentioning
confidence: 53%
“…7 Optical and MO properties of a number of half-metallic FHA's have been investigated theoretically and experimentally. [8][9][10][11][12][13][14][15][16][17] It has been shown that the predictions significantly depend on the calculation methods employed. 12,17 At the same time, the experimental optical and MO properties of the HA's are often quite difficult to explain without first-principle calculations.…”
Section: Introductionmentioning
confidence: 99%